2022
DOI: 10.3389/fendo.2021.802541
|View full text |Cite
|
Sign up to set email alerts
|

The Nuanced Metabolic Functions of Endogenous FGF21 Depend on the Nature of the Stimulus, Tissue Source, and Experimental Model

Abstract: Fibroblast growth factor 21 (FGF21) is a hormone that is involved in the regulation of lipid, glucose, and energy metabolism. Pharmacological FGF21 administration promotes weight loss and improves insulin sensitivity in rodents, non-human primates, and humans. However, pharmacologic effects of FGF21 likely differ from its physiological effects. Endogenous FGF21 is produced by many cell types, including hepatocytes, white and brown adipocytes, skeletal and cardiac myocytes, and pancreatic beta cells, and acts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 222 publications
(471 reference statements)
0
28
0
Order By: Relevance
“…FGF21 response in organs appears to be influenced by tissue-specific interactions ( 68 ), summarized in Figure 1 . FGF21 stimulates adiponectin secretion from adipocytes, which confers metabolic actions on the other cells/tissue, such as blood vessels ( 69 ).…”
Section: Multi-organ Crosstalk Mediated By Fgf21mentioning
confidence: 99%
“…FGF21 response in organs appears to be influenced by tissue-specific interactions ( 68 ), summarized in Figure 1 . FGF21 stimulates adiponectin secretion from adipocytes, which confers metabolic actions on the other cells/tissue, such as blood vessels ( 69 ).…”
Section: Multi-organ Crosstalk Mediated By Fgf21mentioning
confidence: 99%
“… 2 Fibroblast growth factor 21 (FGF21) is a 181 amino acid peptide hormone, primarily released by the liver in response to physiological perturbations, with key functions in the homeostatic control of glucose and lipid metabolism. 3 Both preclinical and clinical studies recently found that alcohol consumption increases endogenous FGF21 levels. 4 , 5 Albeit preliminary, these findings suggest that elevated FGF21 following alcohol use may lead to reduced alcohol intake, potentially through acting on the co-receptor β-klotho (encoded by the KLB gene) expressed in the brain.…”
Section: Main Textmentioning
confidence: 99%
“…While the present study provided important mechanistic information, more research is needed to understand the bidirectional relationship between FGF21 and alcohol ( Figure 1 ). Previous studies found that acute and chronic alcohol consumption in rodents 3 and humans 4 induce hepatic FGF21 and may be dependent on the carbohydrate response element-binding protein (ChREBP) and/or the peroxisome proliferator-activated receptor (PPARα). 3 While ChREBP and PPARα mediate hepatic FGF21 production under fasting conditions, whether alcohol triggers these specific pathways remains unknown.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations